Children's Literature: From English to Portuguese - Silva, Ana Alexandra Lázaro Vieira da (2014)
The subject of this paper is to give the reader an overview of children’s literature and the translation of those books for children. Various aspects of these themes are discussed in order to present a comprehensive overview of the subject. This paper will not detain itself in the definition and review of the concept „children’s literature“, for it is not our main concern in this paper. We’ll be taking a look at an english author, Julia Donaldson. She’s mostly known as the author of The Gruffalo and other stories, many of which are illustrated by Axel Scheffer. It is our intend to observe The Gruffalo the translation process it underwent, from English to Portuguese.